(3SQGL GdXdeIs - (3GdeNJaj, YHO GdcQje Hf jMji Hf YKeGfs
(3ChdgG (B:s
(3HSe Gddg bGd GdTjN GdEeGe ChSe gPG GdcJGH GdPj CPcQ ajg JQcjH GdejGg hgh GSJNQGL GdONGf hGdOgf aj GdHNGQ MJi jchf GdUGHZ hGdeUHhZ UHZG ehdhOG hhGdOG s
(3BNQgG (B:s
(3cYed GdJj GcdJg GdfGQ hCeG GdeQjN gh GdfTGOQ hGdTej gh GdfGQ hGdeGA gh GdHdZe hGdghi gh GdOe hGdfGQ gj GdeQGI GdUaQI hGdCQVjI gjI GdeQGI GdShOGA HGQOI jGHSI hgj gPg ceG JQi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\983s
(3cTa GdXfhf (B2\983s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs